Media coverage and framing of road traffic safety in India - Jagnoor Jagnoor; Margaret Peden; Medhavi Gupta; Inayat Singh Kakar; Elena Altieri (BMJ Global Health, 2021)
Background Media coverage of road traffic collisions (RTCs) may influence preventative action. India experiences some of the highest RTC mortality and morbidity rates globally, but advocacy and effective action to mitigate this has been limited. We conducted an analysis of Indian media in English to assess whether coverage met the WHO’s Reporting on Road Safety guidelines for evidence-based reporting of RTCs.Methods English-language articles published online between March 2018 and February 2019 were assessed against the seven recommended story angles and seven recommended key elements in the WHO guidelines.Results 458 articles were included in the analysis. The most common story angle was descriptions of single collisions, which was not a WHO-recommended story angle. These included limited key elements such as use of human story or linking to road safety risks or evidence-based solutions. However, some articles did follow the WHO-recommended story angles, with 22.1% discussing specific road safety solutions and a further 6.3% discussing vulnerable groups. Almost all articles avoided the use of technical language, but only 2.0% explicitly stated that RTCs were preventable. More than half identified at least one evidence-based solution. Very few articles discussed economic or health impacts of RTCs, including the burden they present to the public health system.Conclusion Indian media in English can improve reporting by focusing on human stories and documenting experiences of those injured in RTCs. Coverage should also focus more on evidence-based solutions, emphasising the systems approach which encourages government action rather than changes to individual behaviour.